Soil-root Shear Strength Properties of Some Slope Plants - Abdullah, M.N.; Ali, F.H.; Osman, Normaniza (Penerbit Universiti Kebangsaan Malaysia, 2011)
Rapid development in hilly areas in Malaysia has become a trend that put a stress to the sloping area. It reduces the factor of safety by reducing the resistant force and therefore leads to slope failure. Vegetation plays a big role in reinforcement functions via anchoring the soils and forms a binding network within the soil layer that tied the soil masses together. In this research, three plant species namely Acacia mangium, Dillenia suffruticosa and Leucaena leucocephala were assessed in term of their soil-root shear strength properties. Our results showed that Acacia mangium had the highest shear strength values, 30.4 kPa and 50.2 kPa at loads 13.3 kPa and 24.3 kPa, respectively. Leucaena leucocephala showed the highest in cohesion factor, which was almost double the value in those of Dillenia suffruticosa and Acacia mangium. The root profile analysis indicated Dillenia suffruticosa exhibited the highest values in both root length density and root volume, whilst Leucaena leucocephala had the highest average of root diameter.